2019
DOI: 10.1007/s12630-019-01508-3
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for article retraction in anesthesiology: a comprehensive analysis

Abstract: Background Increasing awareness of scientific misconduct has prompted various fields of medicine, including orthopedic surgery, neurosurgery, and dentistry to characterize the reasons for article retraction. The purpose of this review was to evaluate the reasons for and the rate of article retraction in the field of anesthesia within the last 30 years. Methods Based on a reproducible search strategy, two independent reviewers searched MEDLINE, EMBASE, and the Retraction Watch website to identify retracted anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…In an analysis of the reasons for retraction in human studies overall, misconduct (51%), errors (14.4%), and duplication (12.6%) accounted for the highest number [12]. A similar trend was seen in anesthesiology where misconduct (specifically fraud or data fabrication) accounted for nearly 50% of all retractions [17]. This pattern was replicated across surgical specialties as well; plagiarism, data falsification, and duplication were the most common reasons for retraction in surgery, orthopedics, and obstetrics and gynecology [6,11,21].…”
Section: Manuscript Characteristics and Reasons For Retractionmentioning
confidence: 78%
See 2 more Smart Citations
“…In an analysis of the reasons for retraction in human studies overall, misconduct (51%), errors (14.4%), and duplication (12.6%) accounted for the highest number [12]. A similar trend was seen in anesthesiology where misconduct (specifically fraud or data fabrication) accounted for nearly 50% of all retractions [17]. This pattern was replicated across surgical specialties as well; plagiarism, data falsification, and duplication were the most common reasons for retraction in surgery, orthopedics, and obstetrics and gynecology [6,11,21].…”
Section: Manuscript Characteristics and Reasons For Retractionmentioning
confidence: 78%
“…The reasons for the retraction of published papers and the rates of retraction vary across scientific disciplines. Data fabrication/falsification, plagiarism, research misconduct, and errors in the articles have been identified to be common reasons for retraction [12,16,17]. In open-access journals, one of the most common reasons for retraction is a compromised peer review process [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, anesthesia appears to have a higher retraction rate than neurosurgery and the HICJ groups; the RI for anesthesia is also higher than that for the life sciences as a whole. Most retractions in anesthesia appear to be due to misconduct by authors, especially data fabrication and plagiarism [20,21]. These reasons for retraction are nearly congruent to those in other specialties [22][23][24].…”
Section: Retractions In Anesthesiamentioning
confidence: 82%
“…Retraction styles vary, and most retractions give clear but limited information. A common view is that academic journals should explain the reasons for retractions in more detail and in a more standardized way (15,16). In this study, sometimes we need some help from PubPeer comments to figure out the reason for retractions, because the retraction notice is not clear.…”
Section: Resultsmentioning
confidence: 99%